Principles of public speaking - German, Kathleen M. (New York Routledge, 2017)
Balancing skills and theory, Principles of Public Speaking, 19th Edition, emphasizes orality, internet technology, and critical thinking as it encourages the reader to see public speaking as a way to build community in today's diverse world. Within a framework that emphasizes speaker responsibility, listening, and cultural awareness, this classic book uses examples from college, workplace, political, and social communication to make the study of public speaking relevant, contemporary, and exciting. This edition opens with a new chapter on speaking apprehension, and offers enhanced online resources for instructors and students.
Speech and higher education -- getting started -- Coping with anxiety -- Critical listening -- understanding your audience -- Finding and using supporting materials -- organizing and outlining your speech -- beginning and ending your speech -- Wording your speech -- Delivering your speech -- Using visual media -- Speeches to inform -- Speeches to persuade -- Argumentation and critical thinking -- Speaking in community settings.
Earlier editions written by Kathleen German and various other authors.
Includes bibliographical references and index.
Keywords: Public speaking